Covariables and types of abnormal left ventricular geometry in nonelderly ischemic stroke survivors: the Norwegian Stroke in the Young Study. Issue 9 (September 2018) - Linde, Anja; Gerdts, Eva; Waje-Andreassen, Ulrike; Pristaj, Nadia; Naess, Halvor; Fromm, Annette; Saeed, Sahrai
Abstract : Background: Abnormal left ventricular (LV) geometry types, like LV hypertrophy (LVH) and concentric remodelling, are independently associated with impaired prognosis in hypertension. Little is known about the prevalence and covariables of abnormal LV geometry types in younger ischemic stroke patients. Methods: We used clinical and echocardiographic data from 280 patients aged 15–60 years included in the Norwegian Stroke in the Young Study. LVH was defined as LV mass index greater than 46.7 g/m 2.7 in women and greater than 49.2 g/m 2.7 in men. Concentric remodelling was considered present if posterior wall thickness/LV internal diameter ratio at least 0.43 in the absence of LVH. Arterial damage was assessed by mean common carotid intima–media thickness (IMT) and carotid–femoral pulse wave velocity (PWV). Results: Abnormal LV geometry was found in 37% of patients. Concentric remodelling was the most prevalent abnormal LV geometry type, found in 21%, whereas LVH was found in 16%. In multivariable logistic regression analyses, LVH was associated with increased PWV, higher BMI and creatinine, and presence of diabetes and hypertension (all P < 0.05), whereas concentric remodelling was associated with higher mean carotid IMT independent of age (both P < 0.05). Conclusion: In ischemic stroke survivors less than 60 years of age, abnormal LV geometry was common, found in 37%. Presence of abnormal LV geometry may contribute to the known higher risk of recurrent cardiovascular events in ischemic stroke survivors.